Molecular evolution in introduced insect species—a mitochondrial perspective - D’Ercole, Jacopo; Vila, Roger; Dapporto, Leonardo; Pentinsaari, Mikko; Talavera, Gerard; Dincă, Vlad; Hebert, Paul D. N. (Frontiers in Ecology and Evolution, 2023)
Abstract Introduced species provide the opportunity to study evolutionary change on short time scales—a key first step to understand and manage the ecosystem-level impact of invasions. This study examined mitochondrial DNA sequence variation in cytochrome c oxidase subunit 1 (COI) for 26 insect species—Coleoptera (9), Hymenoptera (9), and Lepidoptera (8)—introduced to the Nearctic from the Palearctic. A total of 6,302 barcode records were retrieved from BOLD (boldsystems.org) to compare sequence diversity between the native and introduced range. As expected, genetic variation averaged nearly an order of magnitude lower in introduced populations (2.19 × 10-5 substitutions per nucleotide) than in the native range (1.48 ×10-4 substitutions per nucleotide). Nonsynonymous and synonymous changes had a similar incidence in the introduced populations (p-value = 0.83, averaging respectively 1.08 × 10-5 and 1.11 × 10-5 substitutions). By contrast, nonsynonymous changes were ten-fold less frequent than synonymous changes in the native populations (p-value < 0.001, averaging 1.74 × 10-5 and 1.3 × 10-4 substitutions, respectively). Patterns of sequence variation in the introduced range were largely congruent across the three insect orders which suggests that they are produced by general processes. This study explores the molecular evolution of introduced species, a fundamental aspect to improve understanding of their biology and manage their impact on ecosystems.